(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The administrative expulsion of immigrants due to the infringements of the legislation on immigration is actually regulated as an administrative sanction and not only as a limitative measure to be adopted by the administrative authorities in order to reorder a certain sector of activity. It is not a simple alternative to economic penalties, which are the main type of administrative sanction, in general terms. The administrative procedure which necessarily has to be followed in order to declare the sanction of expulsion is quite accurate with the general principles and rules of the administrative procedure, although the so called preferent procedure presents reasonable incompatibilities with those principles and legislation.